Analyzing Contemporary Trends in Sustainable Finance and ESG Investment - Ran Xiao; Jiaqi Deng; Yuting Zhou; Meng Chen (Law and Economy, 2023)
Sustainable finance and Environmental, Social, and Governance (ESG) investment have emerged as critical drivers in the modern financial landscape. This paper explores the contemporary trends in sustainable finance and ESG investment, highlighting the significance of analyzing these dynamics. It delves into the core concepts of sustainable finance and ESG investment, examining their principles and relevance. The paper also discusses current trends, including the importance of impact investing and the role of green finance in climate resilience. ESG integration in investment strategies is a focal point, covering screening, exclusion criteria, and ESG factors in decision-making. Regulatory frameworks, both international and national, and stakeholder engagement, such as corporations, investors, civil society, and consumers, play a pivotal role. Case studies illustrate both successful instances and challenges in sustainable finance, paving the way for a compelling conclusion. The paper concludes by discussing the future prospects and implications, encompassing emerging trends and their impact on the financial industry and society.